Phytotoxicity of leaf aqueous extract of Rapanea umbellata (Mart.) Mez (Primulaceae) on weeds - doi: 10.4025/actasciagron.v35i2.16166 - Novaes, Paula; Imatomi, Maristela; Miranda, Maria Agusta Ferraz Machado; Gualtieri, Sonia Cristina Juliano (Acta Scientiarum. Agronomy, 2012)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> Allelopathic substances can be used to develop weed control alternatives based on natural products. The objective of this study was to compare the phytotoxic activity of aqueous leaf extracts of Rapanea umbellata with the toxicity of a synthetic herbicide on the germination and growth of weed species. The weeds species barnyard grass (Echinochloa crus-galli), wild poinsettia (Euphorbia heterophylla) and morning glory (Ipomoea grandifolia) were used. The effects of the aqueous leaf extract of R. umbellata at concentrations of 10% and 5% (g mL-1) were compared to the control (distilled water) and to the synthetic herbicide oxyfluorfen. The average weed germination time was significantly lower (p < 0.05) in control than in extract and herbicide treatments. The herbicide had more significant effects than the extract on the initial growth of the aerial part. However, the initial growth of the root part was significantly more affected by the leaf extract than by the herbicide. The extract also caused many disorders in weed root anatomy. Therefore, the leaf aqueous extract of R. umbellata showed important results that indicate that it should be bioprospected and that its allelochemicals should be purified for the discovery of natural-origin herbicides. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>